Enforcement of Criminal Law against Foreigners in The Crime of Fraud (A Study of the Application of the Territorial & Fault Principles in Decision No. 161/Pid.B/2019/PN.Mak) - Erni Tyas Aryani; K Kuswardani (Universitas Muhammadiyah Surakarta, 2024)
Criminal law enforcement against foreigners is an important part of international criminal law because Indonesia is a country where foreigners can visit, live and work. law enforcement has the aim of protecting the interests of the state and its citizens and creating order and security in the country. This research focuses on the application of the territorial principle in Decision No.161/Pid.B/2019/PN.Mak and the application of the principle of guilt in the verdict. The method in this research uses normative juridical, in which in this research the author will use Decision Number 161/Pid.B/2019/PN. The results showed that in the case of fraud at Toko Satu Tujuh, the defendant was guilty of intentionally committing fraud with a common plan so that he was sentenced to imprisonment as a consequence of the criminal act he committed.